A Longitudinal Medical School Evidence-Based Medicine Curriculum - Colin West; Thomas Jaeger; Furman McDonald (Association of American Medical Colleges, 2014)
Abstract Introduction Evidence-based medicine (EBM) has become an important component of medical education at all levels. However, lack of knowledge and skills is a key factor limiting EBM application among learners and practicing physicians. Most curricula to date have been seminar series or "short courses," and extended EBM instruction throughout clinical experiences has been only rarely reported. To address this gap, a team of trained EBM experts created an EBM curriculum with both a "short course" component and an extended longitudinal component spanning clinical clerkship experiences. Methods This course involved 18 contact hours in large and small groups at the end of the second year of medical school, prior to beginning third-year clerkship experiences. The students also prepared structured assignments relating to direct clinical care encounters on their core clerkships during the third and fourth years of medical school. These assignments received detailed written evaluation and feedback. Results The curriculum has completed training of six graduating medical classes at the Mayo Medical School, with two more currently engaged in the curriculum. EBM knowledge outcomes of this curriculum have been reported in two publications to date. The curriculum has been associated with substantial improvements in Berlin Questionnaire and Fresno Test of competence in EBM scores, sustained at least through the end of the third-year clerkships. Discussion A critical element of the success of the curriculum has been medical school administration support of integration of the clerkship assignments into each clinical rotation. Common pitfalls include occasional conflicts between what students learn about EBM in the course and what they learn during their clerkships. The course materials could be expanded to include a greater variety of article and clinical question types, but this would exacerbate the demands on the instructors and may not be feasible.